Significance of Abnormal Rabbit Ileal Histology in the Pathogenesis of Diarrhea - Donowitz, Mark (1979)
In spite of several macroscopic criteria for predicting the presence of histological abnormalities in rabbit ileum, microscopic ileal abnormalities still can escape detection. The effect of histologically abnormal rabbit ileum was evaluated on basal intestinal absorption, on basal absorption, on basal adenylate cyclase activity, and on cholera toxin-induced secretion and cholera toxin-induced stimulation of adenylate cyclase activity. Compared to histologically normal rabbit ileum, the presence of histological abnormalities was associated with decreased basal intestinal water, Na, Cl, and glucose absorption, absent glucose-dependent water absorption, and elevated basal adenylate cyclase activities. However, histologically abnormal rabbit ileum responded to inoculation of purified cholera toxin with stimulation of intestinal water secretion and adenylate cyclase activity similar to that in histologically normal ileum. These data have implications concerning the design of experiments that attempt to study the pathogenesis of diarrheal diseases by correlating changes in ileal transport with changes in ileal mucosal adenylate cyclase activity. In spite of abnormal ileal histology, studies of intestinal secretory states which attempt to define the role of adenylate cyclase in secretory processes can be performed provided animals are used as their own controls. However, when groups of animals are compared, the presence of an histologically abnormal ileum can cause changes in basal and intestinal secretagogue-stimulated ileal water and electrolyte transport and in basal and intestinal secretagogue-stimulated mucosal adenylate cyclase activity which can lead to erroneous conclusions if the presence of the abnormal ileal histology is not considered.